Qualitative modeling of multi-stage fractured horizontal well productivity in shale gas reservoir. Issue 4 (July 2017) - Yu, Rongze; Bian, Yanan; Qi, Yadong; Zhang, Jinying; Zhang, Jingping; Zhang, Xiaowei; Guo, Wei; Yan, Jun; Wang, Meizhu
As an important unconventional gas resource, shale gas has become an important part of gas production in recent years with the advantage of horizontal well drilling and large-scale multi-stage hydraulic fracturing completion technologies. The shale gas reservoir numerical simulation advances were reviewed and a multi-stage fractured horizontal well numerical simulation was performed to qualitatively modeling the well productivity in over-pressured shale gas reservoir based on actual shale properties and well completion parameters. A single horizontal well model was established on the basis of dual-porosity model and logarithmically spaced grid refinement. A comprehensive comparison and analysis of the initial average gas production, daily gas production, cumulative gas production, adsorbed gas and free gas cumulative production were provided to investigate the influence of matrix permeability, SRV permeability, hydraulic fracture conductivity and half length, SRV size, bottomhole pressure on the well performance. The research shows that for the high matrix permeability (Km  > 10 −7  mD) and low SRV permeability (KSRV  < 0.01 mD), the SRV permeability has a significant impact on the initial average gas production. For the high matrix permeability (Km  > 10 −7  mD) and medium SRV permeability (0.01 mD < KSRV  < 0.5 mD), the initial average gas production is controlled by both the matrix and SRV permeability. For the high matrix permeability (Km  > 10 −7  mD) and high SRV permeability (KSRV  > 0.5 mD), the initial average gas production is mainly controlled by the matrix permeability. When the matrix permeability is lower than 10 −9  mD, the cumulative gas production is too low to be of economic interest. For the matrix permeability (10 −9  mD < Km  < 10 −5  mD), the matrix permeability and SRV permeability are all important factors that influence the cumulative gas production. For the matrix permeability (Km  > 10 −5  mD), the matrix permeability has much more impact on cumulative gas production than that of SRV permeability. The daily gas production and cumulative gas production are independent of hydraulic fracture conductivity and half length. The initial gas production of multi-stage fractured horizontal well is also independent of SRV sizes. The SRV size mainly controls the gas production decline characteristic. With the increase of the SRV size, the daily gas production declines slowly. The SRV size determines the cumulative gas production directly. With the increase of the SRV size, the cumulative gas production increases linearly. The bottomhole pressure has a significant impact on cumulative gas production. With the decrease of the bottomhole pressure, the cumulative gas production of 20 years increases linearly.